Student Empathy Resilience Design Model in Group Counselling Learning - Indri Astuti; Hastiani Hasti (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
The purpose of this study was to describe a resilience design model in increasing student empathy through group counselling. The research data were collected by survey using inventory and interview instruments. The data were analysed by percentage for the results of the inventory and interview with qualitative descriptions. There were 68 respondents for guidance and counselling students. The results showed that the resilience of students empathy were generally high, meaning that the resilience of students empathy were theoretically high. Furthermore, in order, the highest empathy resilience aspects are optimism, causal analysis, empathy, self-efficacy, reaching out, emotion regulation, impulse control. These findings suggested that students have a strong belief that problems could be solved by the toughness ability to optimize empathy in solving group member problems. Therefore, it was necessary to design a collaboration model between PEDATI and group counselling to increase student empathy through group counselling practice. The design step of the collaborative model of PEDATI and group counselling was systematic and systemic, so that it could serve as a guideline for lecturers and guidance and counselling teachers in carrying out group counselling learning.